“KULTUR SEKOLAH DALAM MENDUKUNG IMPLEMENTASI VISI DAN MISI SERTA PEMBENTUKAN KARAKTER PESERTA DIDIK: STUDI OBSERVASI PLP I DI SMA NEGERI KABUPATEN DELI SERDANG” - Yosefa T D Situmorang; Sepriana Mangisi Tua Manurung; Veronika Tumanggor; Tasya Irene Pandiangan; Sesilia Anju Chrystina Tamba; Zahrawani Dwiyarno (STKIP Subang, 2026)
School culture constitutes one of the determining factors in the successful implementation of a school’s vision and mission as well as the character development of students. This study aims to analyze the role of school culture in supporting the implementation of the school’s vision and mission and the formation of students’ character based on field observations conducted during the School Field Introduction Program I (PLP I) at a state senior high school in Deli Serdang Regency. A qualitative descriptive approach was employed. Data were collected through direct observation, documentation, and document study throughout the PLP I period. Findings indicate that the school has developed various positive cultural practices through the enforcement of school regulations, religious activities, the smile-greet-speak habituation program, as well as cleanliness and social responsibility initiatives. Nevertheless, the implementation of these values still faces several challenges, including inconsistent discipline among some students, uneven learning engagement, suboptimal use of interactive learning media, and limited inclusive facilities. This study concludes that strengthening school culture must be pursued continuously through optimized character development programs, enhanced use of educational technology, and the development of more inclusive educational facilities.